Economic disturbances and equilibrium in an integrated global economy : investment insights and policy analysis - Canto, Victor A.; Wiese, Andy (Academic Press, an imprint of Elsevier, 2018)
Economic Disturbances and Equilibrium in an Integrated Global Economy: Investment Insights and Policy Analysis helps readers develop a framework for analyzing economic events and make better, more consistent decisions. Victor Canto presents the theoretical building blocks that make up the overall framework, then expands the framework to tackle more complex problems, applying additional considerations to actual policy or investment issues. Drawing upon the most recent trends in monetary policy and international economics, the book offers sustained direct engagement with the main research question and makes innovative use of the simple concepts of supply and demand to illuminate modern finance literature. The book succeeds by highlighting the often-forgotten interconnectedness of different economic processes. How do we respond to a change in policy or an economic shock? Are all the expected changes to the general equilibrium consistent with each other?